Suboptimal Partial Transmit Sequence-Active Interference Cancellation with Particle Swarm Optimization. (16th August 2010) - Tarasak, Poramate; Lin, Zhiwei; Peng, Xiaoming; Chin, Francois
Abstract : Active interference cancellation (AIC) is an effective technique to provide interference avoidance feature for an ultrawideband (UWB) OFDM transmitter. Partial transmit sequence-AIC (PTS-AIC), which was recently proposed as an improvement of AIC, requires high computational complexity by doing the exhaustive search of all possible weighting factors whose number grows exponentially with the number of subblocks used. To reduce the complexity of PTS-AIC, this paper proposes a suboptimal way, called particle swarm optimization (PSO), to choose the weighting factors suboptimally without much performance degradation. Both continuous and discrete versions of PSO have been evaluated, and it has been shown that the discrete PSO is able to reduce the complexity significantly without sacrificing the performance of PTS-AIC in many cases.